Learning style and its association with academic performance among physiotherapy students of Universiti Kebangsaan Malaysia - Nor Azura Azmi,; Aimi Hafizah Marzuki,; Mohd Azzuan Ahmad,; Nor Azlin Mohd Nordin,; Mohd Azzuan Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Physiotherapy students require relevant learning style according to years of study in order to optimise learning outcomes. To date, learning styles among this student group are not known. This study aimed to identify the learning styles among physiotherapy students of Universiti Kebangsaan Malaysia and their association with academic performance. A cross-sectional study was conducted involving 61 physiotherapy students. Participants completed a self-administered questionnaire which consists of two sections, namely a demography section and a learning styles section. Questions in the learning style sections were adopted from items of the Kolb Learning Style Inventory. Summary of Kolb Learning Theory and Learning Style Inventory was explained to the participants prior to the questionnaire completion. All data were analysed descriptively and with the use of inferential statistics. All 61 participants returned the questionnaire (response rate of 100%). Results shown that a total of 44.26% (n=27) and 39.30% (n=24) of the participants used Assimilative and Divergent learning style, respectively. Students in the senior year were more likely to utilise divergent learning style as compared to the juniors. However, no significant association was found between learning styles and the academic performance (r=0.02, p=0.801). In conclusion, physiotherapy students of UKM utilise mostly assimilative and divergent learning styles. Both learning styles are considered appropriate for physiotherapy study as watching and thinking concepts, and feeling while processing information are needed especially during clinical practices.